Large‐area atmospheric pressure dielectric barrier discharges in Ar–HMDSO mixtures: Experiments and fluid modelling. Issue 2 (11th November 2019) - Loffhagen, Detlef; Becker, Markus M.; Hegemann, Dirk; Nisol, Bernard; Watson, Sean; Wertheimer, Michael R.; Klages, Claus‐Peter
Abstract: The electrical discharge characteristics of a large‐area experimental dielectric barrier discharge in argon–hexamethyldisiloxane mixtures containing up to about 1, 600 ppm of the monomer is analysed by means of electrical measurements and numerical modelling. A time‐dependent, spatially one‐dimensional fluid model is employed, taking into account the spatial variation of the discharge plasma between the two plane‐parallel dielectrics covering the electrodes. Reasonable agreement between electrical measurements and modelling results is generally found for the gap voltages and discharge currents. Remaining differences between the measured and calculated electrical energy dissipated in the plasma per period are discussed. Abstract : Experimental results of the electrical characteristics obtained in a large‐area dielectric barrier discharge in argon–hexamethyldisiloxane mixtures at atmospheric pressure are compared with a corresponding modelling study. Measured and calculated results agree reasonably well, and certain differences in the electrical energy dissipated in the discharge per period are discussed from different viewpoints.